2005
DOI: 10.1136/thx.2005.041327
|View full text |Cite
|
Sign up to set email alerts
|

Randomised crossover study of pressure and volume non-invasive ventilation in chest wall deformity

Abstract: Background: Non-invasive ventilation is an established treatment for chronic respiratory failure due to chest wall deformity. There are few data available to inform the choice between volume and pressure ventilators. The aim of this study was to compare pressure and volume targeted ventilation in terms of diurnal arterial blood gas tensions, lung volumes, hypercapnic ventilatory responses, sleep quality, and effect on daytime function and health status when ventilators were carefully set to provide the same mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 34 publications
3
49
1
6
Order By: Relevance
“…In previous studies focusing on a heterogeneous population including neuromuscular subjects, VC-CMV NIV was associated with more gastrointestinal adverse effects, 19,20 mainly flatulence, although no differences between the 2 ventilator modes in overall acceptability have been reported. 20,21 Our results show high rates of tolerance, even higher than those reported in studies using PC-CMV NIV, and point to an important role for this ventilator mode when it is initiated in a specific unit for the management of respiratory problems in patients with ALS. The mean set tidal volume used in the present study is in the range of those described in previous studies, and no adverse effects have been reported.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In previous studies focusing on a heterogeneous population including neuromuscular subjects, VC-CMV NIV was associated with more gastrointestinal adverse effects, 19,20 mainly flatulence, although no differences between the 2 ventilator modes in overall acceptability have been reported. 20,21 Our results show high rates of tolerance, even higher than those reported in studies using PC-CMV NIV, and point to an important role for this ventilator mode when it is initiated in a specific unit for the management of respiratory problems in patients with ALS. The mean set tidal volume used in the present study is in the range of those described in previous studies, and no adverse effects have been reported.…”
Section: Discussioncontrasting
confidence: 46%
“…The mean set tidal volume used in the present study is in the range of those described in previous studies, and no adverse effects have been reported. 1,8,21 Survival of subjects with ALS has been shown to be strongly associated with NIV adherence, 3,22 and NIV adherence is a predictor of the improvement produced by NIV in quality of life in subjects with ALS. 4 Our results confirm, in accordance with previous studies, that tolerant subjects use NIV for a longer period before death/tracheostomy (median 22.0 months) compared with intolerant NIV ϭ noninvasive ventilation ALS ϭ amyotrophic lateral sclerosis OR ϭ odds ratio BMI ϭ body mass index ALSFRS-R ϭ revised Amyotrophic Lateral Sclerosis Functional Rating Scale P Imax ϭ maximum inspiratory pressure P Emax ϭ maximum expiratory pressure subjects (median 6.0 months).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Ayrıca basınç ayarlı NIMV maske kaçakları iyi tolere edilir ama inspiratuar basınç hasta eforuna, akciğer kompliyansı ve hava yolu rezistansına bağlı olarak ventilasyonda değişikliklere neden olabilir. [26][27][28][29] Laboratuvarda yapılan model çalışmalarında, pozitif basınçlı ventilatörlerde kaçak kompansasyonu, hastaya verilen tidal volüm ve ayarlanan basınçlar incelendiğinde, ventilatörler arasında farklılıklar olduğu görülmüştür. 26,27 Hasta uyanıkken ayarlanan tolere edebileceği basınç desteği, hasta uyurken noktürnal hipoventilasyonu kontrol etmeyebilir.…”
Section: Bulgularunclassified
“…151 In the past, both modes of NIV have been successfully used in different pathologies, with comparable improvements in gas exchange, lung function, sleep quality, and HRQOL. 152,153 To combine the advantages of pressure-and volumepreset NIV, a hybrid mode called target-volume NIV was introduced over 10 years ago. 151 In this mode, a preset target volume (per breath or per min) and 2 levels of IPAP (minimal and maximal) are combined.…”
Section: Niv Modes: Recent and Future Developmentsmentioning
confidence: 99%